STRATEGI PENGEMBANGAN KOPERASI DI KABUPATEN BURU SELATAN - Djufri Rays Pattilouw (Jurusan Ekonomi Pembangunan, FEB Universitas Pattimura, 2017)
The study aims to identify and map the potential of cooperative development in South Buru Regency, and formulate its development strategy. The analysis used is the Internal Factor Evaluation (IFE) matrix, the External Factor Evaluation (EFE) matrix, the Internal-External matrix (IE), and the matrix Strength-Weakness-Opportunity-Threat (SWOT). The results of the analysis show that most cooperatives in Buru Selatan Regency have internal performance which is relatively inefficient but the external environment is quite conducive. The recommended development strategies are Weakness to Opportunities (W-O) strategy, namely how to fix weaknesses to optimize opportunities. This result implies that in the future the construction of cooperatives in South Buru can be carried out through four important steps, namely 1) Regeneration (re-purification) of the vision, mission and objectives of cooperatives; 2) Reorient the focus of developing cooperative businesses based on local economic potential; 3) Revitalization of cooperative development programs by the government; 4) Reformulation of cooperative business strategies that are more resilient and competitive.